2018
DOI: 10.3390/polym10060636
|View full text |Cite
|
Sign up to set email alerts
|

Inhalable Fucoidan Microparticles Combining Two Antitubercular Drugs with Potential Application in Pulmonary Tuberculosis Therapy

Abstract: The pulmonary delivery of antitubercular drugs is a promising approach to treat lung tuberculosis. This strategy not only allows targeting the infected organ instantly, it can also reduce the systemic adverse effects of the antibiotics. In light of that, this work aimed at producing fucoidan-based inhalable microparticles that are able to associate a combination of two first-line antitubercular drugs in a single formulation. Fucoidan is a polysaccharide composed of chemical units that have been reported to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 56 publications
3
30
0
Order By: Relevance
“…The authors of this paper have reported an application of fucoidan as a matrix material of inhalable microparticles, associating two first-line antitubercular drugs, in a strategy of inhalable tuberculosis therapy. Fucoidan microparticles have shown ability to undergo internalisation by alveolar macrophages and activate the target cells [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this paper have reported an application of fucoidan as a matrix material of inhalable microparticles, associating two first-line antitubercular drugs, in a strategy of inhalable tuberculosis therapy. Fucoidan microparticles have shown ability to undergo internalisation by alveolar macrophages and activate the target cells [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The mass of the particles with a diameter of less than 5 µm can be calculated (this mass otherwise corresponds to the fine particle dose if divided by the number of the applied DPI capsules). A FPF < 5 µm can be obtained from the graph as a percentage of the ED [60]. From the percentage value for 3 µm ( Figure A1, blue line) we can get the mass of the particles with a diameter less than 3 µm, from which we get FPF < 3 µm as a percentage of the ED.…”
Section: Discussionmentioning
confidence: 95%
“…The amounts filled into the capsules were calculated, the MXP content per sample was 1.3 mg [43]. By the investigation, two cycles of inhalation were applied for 4 s. Breezhaler ® (Novartis International AG, Basel, Switzerland) was used as a DPI device with three [60] transparent, size 3 hard gelatin capsules (Coni-Snap ® , Capsugel, Bornem, Belgium). The applied DPI device, the capsules, the mouthpiece, the induction port, the eight plates of the ACI, and the filter were washed with methanol + pH 7.4 phosphate buffer (60 + 40 v/v%).…”
Section: In Vitro Aerodynamic Investigationmentioning
confidence: 99%
“…The comparison of release profiles supports the conclusion that the matrix rules the release pattern. Although ChS is a hydrophilic polymer, it was able to provide a slower release of these drugs in comparison with microparticles composed of fucoidan, another hydrophilic polymer, which has shown a total release of INH and RFB in 30 min [33]. Locust bean gum, in turn, provides more viscous solutions and, thus, sustained the release of INH until 120 min and RFB up to 240 min [34], while low molecular weight chitosan microparticles released completely INH and RFB in 120 min [35].…”
Section: Inh and Rfb Release From Chs Microparticlesmentioning
confidence: 99%